Maldives Economic Update, September 2010 - World Bank (Washington, DC, 2017)
The rebound in tourism experienced since August 2009 seems to have been sustained, auguring well for a sizeable recovery this year from the slump of 2009. Despite having posted better-than-expected fiscal results in the first half of the year, the country will be hard-pressed to sustain this in the medium term. However, despite the challenges, the government remains steadfastly committed to fiscal consolidation. Monetary policy has been made more conducive to sustaining both domestic stability and external stability. Inflation pressures remain modest, with the introduction of non-monetary financing of the deficit. However, the country's turbulent political environment persists, complicating forecasts of future outcomes. The ambitious task of fiscal consolidation and the establishment of macro stability require much political bi-partisanship and cooperation.